Repair of Partial Anomalous Pulmonary Venous Connection to the Azygous Vein via Right Thoracotomy. Issue 2 (March 2023) - Said, Sameh M.; Ricciardi, Gabriella; Smith, Benjamin J.; Sainathan, Sandeep; Narasimhan, Shanti L.
A 21-month-old boy was diagnosed with partial anomalous pulmonary venous connection, with the right upper pulmonary veins draining to the superior vena cava (SVC). Intraoperatively, it became evident that the right upper pulmonary veins connected to the azygous vein before draining to the SVC.